2017
DOI: 10.1111/1468-5973.12155
|View full text |Cite
|
Sign up to set email alerts
|

Deciding to Help: Effects of Risk and Crisis Communication

Abstract: This study aimed to gain insight into the (combined) effects of risk and crisis communication on adequate behaviour during a crisis situation. In addition, it adds to the existing literature by examining the effects of risk and crisis communication on psychological factors that are involved in decision-making during a crisis. This study, utilizing a virtual environment, was a 3 (risk communication: risk information vs. risk information with course of action vs. control) 3 2 (crisis communication: with recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Given warning systems that use these newer media are still relatively new, building trust in these systems is key to effective warning and alert messages (Brynielsson et al, ). Public education should include improving awareness of the warning system, educating the public about how to appropriately respond to these messages, and communicating courses of action during crises (Bakker, Kerstholt, & Giebels, ; Madden, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given warning systems that use these newer media are still relatively new, building trust in these systems is key to effective warning and alert messages (Brynielsson et al, ). Public education should include improving awareness of the warning system, educating the public about how to appropriately respond to these messages, and communicating courses of action during crises (Bakker, Kerstholt, & Giebels, ; Madden, ).…”
Section: Discussionmentioning
confidence: 99%
“…Feng, GonzĂĄlez, Amor, Lovreglio, & Cabrera‐Guerrero, 2018; Kinateder, Comunale, & Warren, 2018; Tucker et al., 2018) and bystander behaviour (e.g. Bakker, Kerstholt, & Giebels, 2018; Buckler et al., 2019). We found that IVET can also be used to conduct rigorous assessment of the impact of discrete message components whilst retaining more realism than other means of conveying emergency scenarios, such as text vignettes.…”
Section: Discussionmentioning
confidence: 99%
“…To discard the doubt about ecological validity, we propose to create a scenario that is more realistic with the help of, for example, virtual reality. In virtual reality, participants could experience sounds and visual stimuli comparable with those experienced in a real‐life emergency, which may therefore lead to feeling more present in the emergency (VR) situation compared to the emergency scenario approach adopted in this study (Bakker, Kerstholt & Giebels, ; van Gelder et al, ). This heightened presence felt in the emergency through the VR approach could trigger different processes in the brain and perhaps tap into the sympathetic nervous system (responsible for the fight‐or‐flight response) which our manipulation probably never did.…”
Section: Conclusion and Discussionmentioning
confidence: 99%